Embracing Indeterminacy: On Being a Liminal Professional. (11th October 2019) - Reed, Cara; Thomas, Robyn
Abstract: The rise of the corporate profession has contributed to a more varied and ambiguous professional terrain that is increasingly seen to be indeterminate and fluid. This paper advances the current debate around the development of corporate professions, exploring how practitioners respond to this environment. Drawing on research with public relations practitioners, the paper shows how the idea of being a liminar facilitates the formation of a professional identity in conditions of high indeterminacy. In taking an individual level of analysis of professions, the paper suggests that indeterminacy is a more resonant feature for corporate professionals than previously suggested in the research, but that this indeterminacy is navigated in professional identity construction through 'being a liminar', and thus greater nuance may need to be recognized in the conceptualization of both corporate professions and corporate professionalization. It also demonstrates the use of liminality as a discursive resource in identity construction and with it, challenges the common association of liminality with self‐doubt and existential anxiety. In turn, the paper considers the implications of the liminal professional identity for the future of contemporary professions, and for understanding the liminal experience.